The Concordance between Mumps and Rubella Sero-Positivity among the Israeli Population in 2015 - Ravit Bassal; Tamy Shohat; Tal Levin; Rakefet Pando; Eilat Shinar; Doron Amichay; Mira Barak; Anat Ben-Dor; Adina Bar-Haim; Ella Mendelson; Dani Cohen; Lital Keinan-Boker; et al. (Vaccines, 2022)
Mumps and rubella are vaccine-preventable viral diseases through the measles-mumps-rubella-varicella (MMRV) vaccine, administered at 12 months and again at 6 years. We assessed the sero-prevalence of mumps and rubella, identified factors associated with sero-negativity, and evaluated concordance between mumps and rubella sero-positivity. A national cross-sectional sero-survey was conducted on samples collected in 2015 by the Israel National Sera Bank. Samples were tested for mumps and rubella IgG antibodies using an enzyme-linked immunosorbent assay. Of 3131 samples tested for mumps IgG, 84.8% (95%CI: 83.5–86.0%) were sero-positive. Sero-negativity for mumps was significantly associated with age (high odds ratios observed in infants younger than 4 years and 20–29 years old subjects). Of 3169 samples tested for rubella IgG antibodies, 95.2% (95%CI: 94.4–95.9%) were sero-positive. Rubella sero-negativity was significantly associated with age (high odds ratios observed in children younger than 4 years old and adults older than 30 years), males, Jews, and others. Concordant sero-positivity for both mumps and rubella viruses was observed in 83.9% of the tested samples. The Israeli population was sufficiently protected against rubella but not against mumps. Since both components are administered in the MMRV vaccine simultaneously, the mumps component has a lower uptake than rubella and quicker waning.